2004
DOI: 10.1093/carcin/bgh096
|View full text |Cite
|
Sign up to set email alerts
|

Plutonium targets the p16 gene for inactivation by promoter hypermethylation in human lung adenocarcinoma

Abstract: Lung cancer from radon or (239)plutonium exposure has been linked to alpha-particles that damage DNA through large deletions and point mutations. We investigated the involvement of an epigenetic mechanism, gene inactivation by promoter hypermethylation in adenocarcinomas from plutonium-exposed workers at MAYAK, the first Russian nuclear enterprise established to manufacture weapons plutonium. Adenocarcinomas were collected retrospectively from 71 workers and 69 non-worker controls. Lung adenocarcinomas were ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(56 citation statements)
references
References 21 publications
1
54
0
Order By: Relevance
“…Exposures to environmental toxicants and toxins might cause epigenetic changes (O'Hagan, 2013;Coppede et al, 2014;Senut et al, 2014) and it is clear that many different adverse environmental factors are likely to exist in the East compared to the West as discussed previously (Nieminen et al, 2012). Our data, together with the available literature (Belinsky et al, 2004;Marsit et al, 2006) suggest a link between environmental exposures, epigenetic changes and experimental models and large series of clinical samples.…”
Section: Discussionsupporting
confidence: 58%
“…Exposures to environmental toxicants and toxins might cause epigenetic changes (O'Hagan, 2013;Coppede et al, 2014;Senut et al, 2014) and it is clear that many different adverse environmental factors are likely to exist in the East compared to the West as discussed previously (Nieminen et al, 2012). Our data, together with the available literature (Belinsky et al, 2004;Marsit et al, 2006) suggest a link between environmental exposures, epigenetic changes and experimental models and large series of clinical samples.…”
Section: Discussionsupporting
confidence: 58%
“…Indeed, a recent study has shown that history of pesticide exposure and more frequently eating food directly from farms were significantly associated with a higher risk of colorectal carcinoma in Egypt (34). However, as the literature on this issue is still sparse (35)(36)(37), the hypothesis that environmental exposures could induce cancers through epigenetic changes remains to be confirmed in experimental models and large series of clinical samples. The Egyptian carcinomas showed MSI rates higher than the Western but MSI was not associated with TSGMP as seen in the Western material.…”
Section: Discussionmentioning
confidence: 99%
“…The most compelling support for DNA damage as an important modifier for methylation comes from studies in humans where increasing exposure to plutonium targeted the p16 gene for inactivation by methylation independent of cigarette smoke. 20 Both plutonium and radon result in the generation of ␣-particles that damage DNA. However, the deposition patterns for these 2 carcinogens differ, with plutonium and radon depositing largely within the peripheral and central lung, respectively.…”
Section: Discussionmentioning
confidence: 99%